PROBLEMATICS IN STRENGTHENING MEMORIALIZATION OF THE QUR'AN ISY KARIMA KARANGANYAR HIGHER SCHOOL OF AL-QUR'AN SCIENCE (STIQ) STUDENTS - Putra, Rizky Pratama; Fatimah, Meti (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Memorizing the Qur'an is not just adding to memorization, but how to maintain memorization that has been memorized. Isy Karima Karanganyar High School of Al-Qur'an Science (STIQ) is one of the Islamic tertiary institutions that organizes tahfihz al-Qur'an as the content contained in the curriculum and all students are required to memorize the Al-Qur'an as their trademark. The research objective was to find out the Problems in Strengthening Students' Al-Qur'an Memorization at the Isy Karima Karanganyar College of Al-Qur'an Studies (STIQ). The type of study is a field study, using a method (field research) with an analytic descriptive approach. The results of the study showed that the problems in strengthening student memorization of the Koran were that some students did not use the right method, felt lazy in repeating memorization, lack of muraja'ah. To overcome these problems, of course there are solutions or ways out to overcome these problems, such as motivating the students, teaching the right methods, and giving good advice.